A Real-World Observation of Eltrombopag and Recombinant Human Thrombopoietin (rhTPO) in Lymphoma Patients With Chemotherapy Induced Thrombocytopenia - Zhu, Qiuhua; Yang, Shimei; Zeng, Wenbin; Li, Mingjie; Guan, Zebing; Zhou, Lanlan; Wang, Hong; Liu, Yanan; Gao, Yanmin; Qiu, Shiqiu; Chen, Chaolun; Li, Huan; et al. (Frontiers in Oncology, 2021)
This real-world, observational study aimed to assess and compare the clinical efficacy and safety of eltrombopag with recombinant human thrombopoietin (rhTPO) in the treatment of chemotherapy induced thrombocytopenia (CIT) in patients with lymphoma. One hundred and fifty-three patients who experienced grade 3 or 4 thrombocytopenia after chemotherapy for lymphoma were enrolled, 51 of which were treated with eltrombopag, 50 with rhTPO, and 52 patients with no drug treatment were served as the control group. The lowest platelet level and mean platelet counts at Day 5 and Day 10 were significantly higher in both the eltrombopag group (P=.041, .003, .000) and rhTPO group (P=.005, .005, .000) than the control, but there was no difference between treatment with eltrombopag and rhTPO. Similarly, days required for the recovery of platelet counts to ≥50×109/L and ≥75×109/L were not different between the two treatment groups but significantly higher than the control group (P <.05). Rates of bleeding and platelet transfusion were all significantly reduced in patients treated with eltrombopag (P=.031, .032) or rhTPO (P=.017, .009) when compared to the control. Treatment-related adverse events (AEs) were reported in 7 (13.7%) and 6 (12.0%) patients in the eltrombopag and rhTPO groups, respectively, all being mild and transient in nature. In conclusion, both eltrombopag and rhTPO were effective and safe in the treatment of thrombocytopenia after chemotherapy for lymphoma.